3-5 風圧下での高速曳航いけすの針路安定性能 - 上田, 耕平; 中山, 博; 重廣, 律男; 有井, 俊彦 (関西造船協会講演論文集, 1997)
The high-speed-towed fish preserve is a new type vessel about 15.6m long with a fish preserve capacity of 200m^3.The ship is supposed to be towed efficiently with a lighter draft(about 0.8m)at a maximum speed of about 10 knots(Fn=0.42).The lateral area ratio between a supper structure and a hull is about 5.3 in a lighter draft.The course stability of the ship might be affected by the wind forces and wave forces.Especially the wind forces are stronger than wave forces in a lighter draft.In this paper, we present the course stability characteristics of the towed fish preserve with wind effects in high-speed range.We conducted the model experiment tests in wind tunnel and in a circular tank.Also we performed the simulation studies to investigate the course stability for our models.The results of our experiments and simulation studies are described and discussed.